2007
DOI: 10.1103/physrevb.76.035105
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium transport and optical properties of model metal–Mott-insulator–metal heterostructures

Abstract: Electronic properties of heterostructures in which a finite number of Mott-insulator layers are sandwiched by semi-infinite metallic leads are investigated by using the dynamical-mean-field method combined with the Keldysh Green's function technique to account for the finite bias voltage between the leads. Current across the junction is computed as a function of bias voltage. Electron spectral functions in the interacting region are shown to evolve by an applied bias voltage. This effect is measurable by photo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 54 publications
1
58
0
Order By: Relevance
“…Along this line, Okamoto investigated the current-voltage (I-V ) characteristics of heterostructures that consist of Mottinsulator layers sandwiched by metallic leads by combining the dynamical mean-field theory with the Keldysh Green's function technique. 20,21 Ajisaka et al studied the I-V characteristics of an electron-phonon system coupled with two reservoirs by a field-theoretical method.…”
Section: -12mentioning
confidence: 99%
“…Along this line, Okamoto investigated the current-voltage (I-V ) characteristics of heterostructures that consist of Mottinsulator layers sandwiched by metallic leads by combining the dynamical mean-field theory with the Keldysh Green's function technique. 20,21 Ajisaka et al studied the I-V characteristics of an electron-phonon system coupled with two reservoirs by a field-theoretical method.…”
Section: -12mentioning
confidence: 99%
“…XA and XMCD spectra of the Ru M 3, 2 edge showed a dichroism signal compatible with ruthenium in an octahedral environment expected in SRO ( Figure XX). [16] Magnetic measurements were taken with a SQUID magnetometer as a function of field and temperature. We found that for all substrate types, (110) films had larger moments than (001) oriented films.…”
mentioning
confidence: 99%
“…The usual way to treat such steady state situation (see, e.g. 37,38 ) is to start at t = −∞ with three decoupled (v l = v r = 0) systems consisting of the two leads plus the central region which are separately in equilibrium at different chemical potentials and temperatures. Then one switches on the hybridisation and waits until a steady state is reached.…”
Section: A Modelmentioning
confidence: 99%